Late-life depression and cognitive function among older adults in the U.S.: The National Health and Nutrition Examination Survey, 2011–2014. (April 2019) - Wei, Jingkai; Ying, Meiling; Xie, Liyang; Chandrasekar, Eeshwar K.; Lu, Haidong; Wang, Tiansheng; Li, Changwei
Abstract: Discrepancies exist on the associations of late-life depression with cognition, and synergistic effect of depression and diabetes on cognition among older adults was suggested in literature. We aimed to examine the associations of late-life depression with cognitive function in a representative sample of older adults in the U.S., and to examine the associations among individuals with diabetes. A total of 3101 adults aged 60 and above of the 2011–2014 National Health and Nutrition Examination Survey who completed measurements of depressive symptoms and diabetes were included in cross-sectional analyses. The 9-item Patient Health Questionnaire (PHQ-9) was used to measure depressive symptoms (including overall, somatic and cognitive). Clinically relevant depression (CRD) and clinically significant depression (CSD) were defined by cutoffs of PHQ-9. Domain-specific cognitive function was examined using Delayed Word Recall Test, Digit Symbol Substitution Test, and Animal Fluency Test for memory, executive function/processing speed, and language, respectively. Z scores were created for overall cognition and specific domains. Multivariable linear regression models were applied to examine the association of depressive symptoms and scale-defined depression with cognition z scores. The overall, somatic and cognitive depressive symptoms were associated with lower cognitive function among older adults. Both CRD (β = −0.20, 95% CI: −0.28, −0.12) and CSD (β = −0.56, 95% CI: −0.75, −0.37) were associated with lower cognition. A synergistic relationship was found between depression and diabetes on lower cognition. These results suggested that cognition among older adults may be modified by late-life depression, and older adults with both depression and diabetes may be particularly impacted on cognition. Highlights: Depressive symptoms, including total, somatic and cognitive symptoms, are associated with lower cognitive function among older adults. Scale-defined depression, including clinically relevant depression and clinically significant depression are associated with lower cognitive function among older adults. Depression and diabetes showed synergistic relationship on cognitive function among older adults.